2022
DOI: 10.1038/s41598-022-07987-7
|View full text |Cite
|
Sign up to set email alerts
|

Piezo2 expression and its alteration by mechanical forces in mouse mesangial cells and renin-producing cells

Abstract: The kidney plays a central role in body fluid homeostasis. Cells in the glomeruli and juxtaglomerular apparatus sense mechanical forces and modulate glomerular filtration and renin release. However, details of mechanosensory systems in these cells are unclear. Piezo2 is a recently identified mechanically activated ion channel found in various tissues, especially sensory neurons. Herein, we examined Piezo2 expression and regulation in mouse kidneys. RNAscope in situ hybridization revealed that Piezo2 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
(81 reference statements)
1
13
0
Order By: Relevance
“…PIEZO2 encodes a sensor for mechanical forces in mesangial cells and renin-producing cells [53]. During dehydration, PIEZO2 expression is down-regulated in mesangial cells and up-regulated in juxtaglomerular renin-producing cells, and there is overproduction of renin and renin-producing cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PIEZO2 encodes a sensor for mechanical forces in mesangial cells and renin-producing cells [53]. During dehydration, PIEZO2 expression is down-regulated in mesangial cells and up-regulated in juxtaglomerular renin-producing cells, and there is overproduction of renin and renin-producing cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…During dehydration, PIEZO2 expression is down-regulated in mesangial cells and up-regulated in juxtaglomerular renin-producing cells, and there is overproduction of renin and renin-producing cell proliferation. The expression of renin is also reduced by PIEZO2 knockdown in juxtaglomerular cells, which demonstrates that PIEZO2 is an important regulator of glomerular filtration and body fluid status [53]. PIEZO2 is also a mechanical sensor for bladder tension [54, 55].…”
Section: Discussionmentioning
confidence: 99%
“…At variance, Mochida et al 117 found that PIEZO2 was expressed in glomerular mesangial cells and renin-producing juxtaglomerular cells at both the mRNA and protein levels. Prior single-cell RNA sequencing of mouse glomerular cells showed that PIEZO2 was expressed at low levels in juxtaglomerular cells.…”
Section: Role Of Piezos In the Kidneymentioning
confidence: 97%
“…80 Additionally, it has been reported that glomerular mesangial cells and renin-producing cells express Piezo2, which was upregulated with renin overproduction in renin-producing cells in response to dehydration as a mechanical load reduction. 81 Whether in vivo loss of function of either Piezo1 or 2 affects renin expression remains to be determined. Other mechanosensitive ion channels, such as the Trpv4 (transient receptor potential vanilloid 4), have been reported to induce pressure-induced calcium transport and inhibit renin secretion.…”
Section: Nuclear Mechanotransduction and The Renin Cell Baroreceptormentioning
confidence: 99%